2003
DOI: 10.1007/s00213-003-1538-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment decreases nicotine-induced hyperactivity in rats

Abstract: These results suggest that environmental enrichment during development reduces the stimulant effect of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
62
3
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 23 publications
6
62
3
4
Order By: Relevance
“…This finding is consistent with previous observations that EC rats display less activity in an inescapable novel environment (Lore and Levowitz, 1966;Fuller, 1967;Bowling et al, 1993;Smith et al, 1997;Green et al, 2003), respond less for a weak auditory stimulus in the absence of consummatory reward (Rose et al, 1986), and have lower response rates on a DRL-20 s operant task (Ough et al, 1972). Since EC rats tend to have reduced locomotor activity compared to IC rats, it could be argued that the effects observed in these studies are simply due to the lower baseline activity of EC rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous observations that EC rats display less activity in an inescapable novel environment (Lore and Levowitz, 1966;Fuller, 1967;Bowling et al, 1993;Smith et al, 1997;Green et al, 2003), respond less for a weak auditory stimulus in the absence of consummatory reward (Rose et al, 1986), and have lower response rates on a DRL-20 s operant task (Ough et al, 1972). Since EC rats tend to have reduced locomotor activity compared to IC rats, it could be argued that the effects observed in these studies are simply due to the lower baseline activity of EC rats.…”
Section: Discussionsupporting
confidence: 93%
“…In this paradigm, rats are housed for several weeks with either social cohorts and novel objects in an enriched condition (EC) or individually without objects in an isolated condition (IC). EC rats subsequently display less activity than IC rats in an inescapable novel environment (Lore and Levowitz, 1966;Fuller, 1967;Bowling et al, 1993;Smith et al, 1997;Green et al, 2003). EC rats also approach novelty more quickly than IC rats in a freechoice test (Fuller, 1967;Renner and Rosenzweig, 1986;Widman and Rosellini, 1990), suggesting that EC rats may find novel stimuli to be less stressful.…”
mentioning
confidence: 99%
“…Previous work has shown that EC rats are less sensitive than IC rats to the hyperactivity observed following acute nicotine (Green, Cain, Thompson, & Bardo, 2003) or acute morphine (Bardo, Robinet, & Hammer, 1997), but not following acute amphetamine (Bowling & Bardo, 1994). Taken together, these results indicate that the effect of environmental enrichment on the psychostimulant effect of drugs is pharmacologically specific.…”
Section: Discussionsupporting
confidence: 55%
“…The hyperactivity produced by acute stimulant treatment is blunted in IC rats relative to EC rats Bowling and Bardo, 1994;Bardo et al, 1995); one exception, however, is that nicotineinduced hyperactivity is increased in IC rats (Green et al, 2003). In contrast to acute treatment, repeated stimulant treatment, including nicotine, is increased in IC rats relative to EC rats (Bardo et al, 1995;Funk et al, 2005;Solinas et al, 2009;Wooters et al, 2011).…”
Section: B Social Influencesmentioning
confidence: 88%
“…IC rats also display a leftward shift in the cocaine dose response curve compared with SC rats (Howes et al, 2000), indicating that isolation housing enhances sensitivity to stimulant reinforcement compared with social housing. However, the presence of novel objects also plays a role, as the behavioral responses to stimulants, opiates, and alcohol differ between SC and EC animals (Bardo et al, 2001;Green et al, 2003;Coolon and Cain, 2009;El Rawas et al, 2009;de Carvalho et al, 2010).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%